Assessing Big Data Analytics and Characteristics in Tourism: Agodi Gardens, Ibadan, Nigeria - olawuyi, Olakunle shakur (Turizam, 2024)
There is a plethora of both organized and haphazard data in tourism destinations. Subjecting these data to appropriate analytics is pertinent to optimally engage them. This study focuses on the connection between big data analytics and big data’s characteristics in Agodi Gardens, Ibadan, Nigeria. Data was collected with questionnaire. The collected data was analyzed descriptively and inferentially. The study revealed that relationship exists between prescriptive/descriptive big data analytics and the characteristics of big data. Precisely, there is significant relationship between prescriptive data analytics velocity, veracity, volume and value. Similarly, there is significant relationship between descriptive data analytics and volume, variety, value and veracity. Likewise, variety and veracity of big data could influence big data analytics. The study therefore recommends; that the management of Agodi Gardens should engage thorough big data analytics, so that data elicited by customers can be appropriately analysed and topical inference could be drawn from the analysis.Keywords: velocity of big data, veracity of big data, volume of big data, value of big data, variety of big data and big data analytics.